Arranjos de governança e gestão da inovação aberta no governo local do Recife após o marco legal das startups - Luciana Sousa Camargos (2024)
The Startup´s Law, published in 2021, recognizes the role of the State in promoting innovative entrepreneurship, encourages actions between the public-private sectors and regulates public administration hiring of innovative solutions designed or developed by startups to solve public problems. However, regulation alone may not be able to achieve this aim. The incorporation of the law benefits depends on how the public organization formulates its strategic orientation in open innovation, issues regulations and employs resources to strengthen its governance arrangements aimed at assimilating technological risk and structuring the open innovation process. The Recife´s Local Government innovation management incorporates, in a pioneering way, among Brazilian capital cities, the law benefits. By implementing the I Open Innovation Cycle, between November 2021 and August 2022, as a result of its governance arrangements, it encouraged the entrepreneurship of startups, at the same time as selected non-functional prototypes, experimented MVPs, and assimilated process technological risks, and, mainly, hired and incorporated innovative solutions into public management in response to the city's challenges. Based on a four-dimensional model, the interpretive qualitative research presents the governance arrangements that determine innovation in Recife´s Local Government, the open innovation management, as well addresses its antecedents and results.